Cars and motorcycles - Townsend, John, 1955- (Chicago : Raintree, 2012)
Explains how science and technology influence the designs of cars and motorcycles, describes the forces that act on vehicles, how they are controlled, and what they are made of, and discusses intelligent cars, friction, hybrid cars, and other related topics.
Science on wheels -- Force -- Blast force -- Speed -- Auto racing -- Grip -- Crash science -- At the cutting edge -- Future technology -- Tomorrow's world -- Timeline -- Quiz -- Glossary -- Find out more -- Index.
"Revealed"--Cover.
Includes bibliographical references (p. 46) and index.
6.2
5-8
5-8
Keywords: Automobiles -- Design and construction -- Juvenile literature; Automobiles -- Dynamics -- Juvenile literature; Motorcycles -- Design and construction -- Juvenile literature; Motorcycles -- Dynamics -- Juvenile literature; Automobiles -- Design and construction; Automobiles -- Dynamics; Motorcycles -- Design and construction; Motorcycles -- Dynamics; Automobiles -- Design and construction; Motorcycles -- Design and construction